ENGLISH BORROWINGS AND SCALE OF BORROWABILITY IN VIETNAMESE MAGAZINES - Nga, Nguyen Thuy (VNU Journal of Foreign Studies, 2017)
When two or more languages are in contact, it is impossible for them to remain completely discrete from each other and the most frequently encountered product of language contact is lexical borrowing. This paper reviews the background of lexical borrowing in Vietnamese context and investigates the scale of borrowability of English tokens that occured in magazine issues. The findings show that the syntactic system of the Vietnamese language has influenced how English word types are borrowed.